The Feasibility Development of Android-Based Application Media (Skeletonpedia) In Biological Learning on Skeletal Systems Submaterial of Senior High School In XI Grade - Ramadhani Nur Aisyah; Widowati Budijastuti (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2020)
Existence of learning media is the facilitates of the learning process for fulfilled the needs for rapid information in the teaching and learning process between student and teacher. Android-based media application are one of the alternative media learning that can be used in the learnt of the skeletal system. The aims of the research was to produce Skeletonpedia as an android-based media application that were practice and valid. This study used the ASSURE development model with 20 students at the second grade of senior high school at SMAN 1 Gedangan. The research instruments were media validation sheets, observation of student activities sheets and student questionnaire response sheets. The results of this study got 3.86 scores with a very valid category of the validity Skeletonpedia as an android-based media application. The practicality of the media got a very practical category based on the use of media by 100% score and student responses by 91.3% score. Based on the researched of the the feasibility in android-based application media of Skeletonpedia on skeletal system submaterial had been proved it as a valid and practical learning media.